Консервация исходных вариантов фразеологических оборотов в системе диалекта (на примере говоров Низовой Печоры) - Урманчеева, ИрИна СерафИмовна (Acta Neophilologica, 2019)
Dialect systems, especially island and resettlement, are more conservative and less dynamic in comparison with an actively developing literary language. The oral form of existence of a dialect predetermines a careful attitude to the language and cultural facts leading to the self-identification of an ethnoconfessional community. The preser- vation – in dialects of Local (Lower) Pechora of the Ust-Tsilemsky Region of the Komi Republic of the Russian Federation – of options of phraseological units which, having undergone lexical, structural or semantic transformation, have become steady turns of the literary language is discussed in this article